Increasing Business Capacity for Processed Marine Food Products for Coastal Women - Saadah, Mar Atun; Sampoerno, Mohd. Norma (GUYUB: Journal of Community Engagement, 2025)
This community engagement program aims to provide training and assistance in enhancing the capacity of seafood processing businesses managed by women in coastal areas of Tanjung Jabung Barat, Sumatra. Local seafood products such as kletek and shrimp crackers are among the region’s leading commodities. However, these businesses are still considered secondary sources of income and lack the necessary legal certifications for market expansion.This program employs a capacity-building approach by facilitating business legality processes, including obtaining Halal Certification (HC), Business Identification Number (NIB), and Home Industry Food Production License (PIRT). The program is designed to fully involve business owners in training and mentoring activities. The training sessions begin with theoretical materials to enhance participants' understanding of business legality, halal compliance, and certification procedures. Practical sessions follow, where participants receive guidance on obtaining NIB, PIRT, and preparing the Halal Product Assurance System (HPAS) documents through the Sihalal platform. The results indicate a significant increase in participants' knowledge regarding the importance of business legality and halal certification processes. Additionally, there was a behavioral shift, as participants who initially lacked the ability to process business legality independently became capable of accessing various online platforms for business registration and certification. This program thus contributes to strengthening the competitiveness of seafood processing businesses led by coastal women in Tanjung Jabung Barat..